REAL WORLD EVIDENCE AND BIG DATA - Mehmet Güven Günver (Sabiad)
Knowledge has been the key to better organization and new developments. With more information, what kind of arrangement and organization is needed to present the best? Indeed, data collection on its subject is an essential part of any organization. Beyond the purpose of accurately reflecting the current status of certain criteria, these data can also be used for anticipatory-predictive prediction of future trends, and this process is carried out considering that this can have many benefits. Today, this knowledge accumulation and evaluation effort has created the need to deal with tons of data from all areas of our lives such as security, social activities, science, work, and health. But after a point, this ‘data storm’ flow, provided by current technologies, became unmanageable with the technologies at hand, the number of experts who could evaluate and interpret, and the time that could be allocated. In this way, the term ‘big data’ was coined to describe large and no longer adequately manageable data. Now there is a need for new strategies that will allow us to organize the data and produce useful information, to use this big data to meet various future needs. This has become so important that a new field of science called ‘data Science’ has emerged. data science; It deals with data management for the flow, storage, classification-management of data and its analysis in order to obtain deeper estimations, and it is of great importance in the functionality or services of the system that will provide this.